1978
DOI: 10.1016/s0022-5347(17)57099-8
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Prophylactic Low Dose Heparin in Transurethral Prostatectomy

Abstract: Low dose heparin prophylaxis has proved effective in reducing postoperative thromboembolic complications in a series combining multiple types of surgical procedures. Our series comfirms its safety for transurethral operations. We recommend its use in patients with predisposing factors to thromboembolic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Of drugs contributing to haemorrhage after prostatectomy the most commonly studied is heparin, administered subcutaneously as prophylaxis for venous thrombo-embolism. Conflicting results have been reported (Halverstadt et al, 1977;Kass et al, 1978;Sleight, 1982;Bejjani et al, 1983;Wilson et al, 1988). There have been few studies on the effect of aspirin on post-prostatectomy haemorrhage but its effect after other surgical procedures is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Of drugs contributing to haemorrhage after prostatectomy the most commonly studied is heparin, administered subcutaneously as prophylaxis for venous thrombo-embolism. Conflicting results have been reported (Halverstadt et al, 1977;Kass et al, 1978;Sleight, 1982;Bejjani et al, 1983;Wilson et al, 1988). There have been few studies on the effect of aspirin on post-prostatectomy haemorrhage but its effect after other surgical procedures is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed relating the use of subcutaneous heparin to blood loss during TURP, but their results are conflicting. Halverstadt et al (1977), Allen et al (1 978) and Sleight (1982) concluded that subcutaneous heparin increased haemorrhage, whereas Kass et al (1978), Miller and Butz (1981) and Bejani et al (1983) concluded that it did not. Most of these studies were either retrospective or used historical controls.…”
mentioning
confidence: 99%
“…In TIJRP, postoperative blood loss can be accurately measured, allowing objective determination of bleeding possibly induced by heparin or associated compounds (14). Previous studies using standard heparin were controversial showing results of either increased blood loss, or no effect on postoperative haemorrhage (17, 18,19). It has been claimed on the basis of animal experiments that LMW heparins and heparinoids caused less bleeding than standard heparin (3, 4,20) .…”
Section: Discussionmentioning
confidence: 99%